Chicken Manure and Mushroom Residues Affect Soil Bacterial Community Structure but Not the Bacterial Resistome When Applied at the Same Rate of Nitrogen for 3 Years - Peng, Shuang; Wang, Yiming; Chen, Ruirui; Lin, Xiangui (Frontiers in Microbiology, 2021)
Animal manure is a reservoir of antibiotic resistance genes (ARGs) and direct application of the manure will lead to spread of ARGs in farmland. Here, we explored the impacts of chicken manure and heat treated chicken manure on the patterns of soil resistome after three years application, with mushroom residue set as the plant derived organic manure treatment. A total of 262 ARG subtypes were detected in chicken manure using high-throughput qPCR, and heat treatment can effectively remove 50 types of ARGs. Although ARGs subtypes and abundance were both higher in chicken manure, there was no significant difference in the ARGs profiles and total ARGs abundance among three manure treated soils. Soil bacteria community compositions were significantly different among manure treated soils, but it was not significantly correlated with soil ARGs profiles. Fast expectation-maximization microbial source tracking (FEAST) was used for quantifying the contributions of the potential sources to microbial taxa and ARGs in manure fertilized soil. Results revealed that only 0.2% of the chicken manure derived bacterial communities survived in soil, and intrinsic ARGs was the largest contributor of soil ARGs (95.8-99.7%), ARGs from chicken manure only contributed 0.4%. The total ARGs abundance in the heat-treated chicken manure amended soils was similar to that in the mushroom residue treated soils, while it was 1.41 times higher in chicken manure treated soils. Thus, heat treatment of chicken manure may efficiently reduce ARGs introduced into soil and decrease the risk of dissemination of ARGs.